Interrelationship and Heritability of Yield and its Components in Chickpea Crosses Differing for Harvest Index - Manpara, B A; Gaikwad, S R (Annals of Arid Zone, 2016)
The study was undertaken on heritability, association and path analysis for seed yield and its components in three F2 populations of chickpea. Parents involved in the cross combinations with varying level of harvest index expressed fairly wide range of variation for other characters too. High heritability (>60%) coupled with high genetic advance (>20%) were observed for plant height, primary branches per plant, pods per plant and seeds per plant. Seed yield per plant showed significant positive correlation with seeds and pods per plant, total biomass per plant and 100-seed weight. Associations were strong and positive among the days to flowering, flowering period and days to maturity, but they were not correlated with seed yield per plant. Path analysis indicated that seeds per plant had maximum direct effect on seed yield followed by 100-seed weight. Pods per plant and total biomass per plant contributed substantially to seed yield via seeds per plant. Therefore, it was concluded that seed yield in chickpea may be improved by selecting for more seeds and pods per plant with higher biomass yield. To break down the undesirable linkages between two important yield components like total biomass per plant and harvest index as indicated by negative correlation between them and to recover the suitable recombinants, biparental mating is suggested. Key words: Cicer arietinum, yield components, heritability, correlation, path analysis.